REALIZATION OF PANCASILA STUDENT PROFILE AT SMA NEGERI 2 AMBON AND ITS IMPACT ON STUDENTS' NATIONAL IDENTITY IN 21ST CENTURY EDUCATION - Sainfalak, Mayo; Marantika, Juliaans E. R.; Tomasouw, Jolanda (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2024)
This research aims to describe the embodiment of the Pancasila student profile at SMA Negeri 2 Ambon in the context of 21st century education, as well as describe the impact of the Pancasila student profile on the national identity of students at SMA Negeri 2 Ambon in the educational era of the 21st century. The research method used in this research is a qualitative method. This method involves collecting descriptive and interpretive data, such as observation, interviews, and document analysis. The research results show that the profile of Pancasila students at SMA Negeri 2 Ambon reflects the school's commitment to producing individuals who are not only academically intelligent, but also have high national awareness, relevant 21st century skills, and a passion to contribute to building a better society. Good. The positive impact seen in students' national identity, such as strengthening national identity, forming a strong nationalist character, increasing multicultural awareness, readiness to face global challenges, and forming quality future leaders, shows that the implementation of Pancasila values has great relevance in responding to the demands of 21st century education. This research provides an important contribution to our understanding of the manifestation of the Pancasila student profile at SMA Negeri 2 Ambon and its impact on the national identity of students in 21st century education. The findings from this research can be a basis for developing more effective educational strategies and policies in the future, as well as providing inspiration for other schools in strengthening the realization of the Pancasila student profile at SMA Negeri 2 Ambon and its impact on the national identity of students in 20th century education. -21.